Intertidal Creeks and Overmarsh Circulation in a Small Salt Marsh Basin. Issue 2 (9th February 2019) - Sullivan, Jessica Chassereau; Torres, Raymond; Garrett, Alfred
Abstract: The role of intertidal creek networks in overmarsh circulation is not well constrained. In this study, we systematically remove intertidal creeks from a high‐resolution salt marsh digital elevation model and conduct new flow simulations with each iteration. Overall, removal of first‐ and second‐order creeks reduced drainage density by 65%, and this had a negligible effect on overmarsh circulation and tracer distribution. However, upon removal of third‐ and fourth‐order creeks, drainage density was reduced by 80% of the original value, and changes in peak velocity magnitude across various spatial and temporal scales reveal a system‐wide switch from ebb to flood dominance. This response coincides with the interruption of topographically connected creeks that facilitate the direct exchange of water and tracer between the marsh interior and the larger subtidal system. Further, this reduction in hydraulic connectivity gives rise to less expansive tracer dispersal and a systematic decline in tracer residence time. Together, these results reveal that for the Groves Creek marsh, lower‐order intertidal creeks have a minor role in overmarsh circulation, while higher‐order creeks increase the potential for short circuiting of flow; they greatly influence overall flood and ebb dominance, and net tracer dispersal and associated retention time. Results reported here provide new insight on, for example, salt marsh restoration and the requisite digital elevation model bathymetry for robust simulations of overmarsh circulation. Key Points: First‐ and second‐order creeks play a minor role in overmarsh circulation Higher‐order creeks are associated with short‐circuiting conduits and greatly impact overmarsh flow, tracer movement, and residence time Salt marsh DEMs must resolve the length scale associated with hydraulic connectivity, but not the smallest intertidal creeks